Beyond the multiplex : cinema, new technologies, and the home - Klinger, Barbara, 1951- (University of California Press, 2006)
Presents a study of how contemporary entertainment technologies and media shape our encounters with movies. This book explores topics, such as home theater, film collecting, classic Hollywood movie reruns, repeat viewings, and Internet film parodies, providing a multifaceted view of the presentation and reception of films in US households.